2020
DOI: 10.1177/0003134820972098
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Outbreak on the Emergency Presentation of Acute Appendicitis

Abstract: Background The global crisis resulting from the coronavirus pandemic has imposed a large burden on health systems worldwide. Nonetheless, acute abdominal surgical emergencies are major causes for nontrauma-related hospital admissions and their incidences were expected to remain unchanged. Surprisingly, a significant decrease in volume and a higher proportion of complicated cases are being observed worldwide. Methods The present study assesses the local impact of the coronavirus pandemic on the emergency presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…26 studies described a change in case number of appendicitis and/or appendectomies between comparable time periods before and during the COVID-19 pandemic in adults [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. Studies were conducted in 15 countries (as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…26 studies described a change in case number of appendicitis and/or appendectomies between comparable time periods before and during the COVID-19 pandemic in adults [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. Studies were conducted in 15 countries (as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During the pandemic period, it was observed that fewer people applied to the emergency services, causing the diseases that these people applied to progress more [ 4 ]. In many studies, it is stated that admissions have increased due to complicated appendicitis [ 4 , 5 ]. Finkelstein et al stated that during the COVID-19 quarantine, there were more patients presenting with perforated appendicitis compared to the same period of the previous year, possibly due to observance of quarantine restrictions and fear of contracting COVID-19 in the hospital [ 6 ].…”
mentioning
confidence: 99%
“…Lower length of hospital stay is desired and favored during the pandemic to decrease the contamination of Cov19 and to empty the beds for a new outbreak. Some studies reported no differences in LOS between these periods [16][17]; however, Kvasnovsky et al [18] reported a significantly higher LOS for AA during the pandemic. Conservatively treated AA patients had longer LOS than the operated patients in both periods [14,19].…”
Section: Discussionmentioning
confidence: 98%
“…Gao et al [33] reported an increased rate of complicated appendicitis due to delayed admission or surgery and decreased P a g e | 911 intention to seek treatment at Cov19. Fonseca et al [17] reported the rate of complicated AA as 15.2% in the pre-pandemic period, and as 33.3% during the pandemic. In our study, the lower rate of complicated AA and luminal pathology implied the accurate indication and timing of appendectomy during the pandemic.…”
Section: Discussionmentioning
confidence: 99%